Deconstructing sport and performance psychology consultant: Expert, person, performer, and self-regulator - Poczwardowski, A. (International Journal of Sport and Exercise Psychology, 2019)
Sport and performance psychology (SPP) consultants play a critical role in successful service delivery. This article inspects the consultant as an expert, person, and performer, which the three aspects are further linked through a self-regulatory (meta-cognitive) function (i.e. consultant as a self-regulator). It will be proposed that not only self-regulation is an important tool in promoting effectiveness of service delivery, but also adds to the consultant`s growth in becoming a more fulfilled human while pursuing excellence in SPP consulting. In particular, the value of self-reflection, deliberate self-regulation, and professional interactions (e.g. supervision, collegial consultations) will be underscored. Theory-driven, empirically grounded, and professional practice founded implications for consultancy, graduate teaching, and applied research will be offered.